Growth Of Sbi Green Channel In India - Arvind Singh Vijay, (Research Inspiration, 2016)
State bank of India green channel very important Indian country State Bank of India (SBI) will introduce “green-channel banking” at more of its branches to promote very important paperless work and to facilitate faster transactions for customers, SBI sources said. Indian country all major transactions, including withdrawals, deposits, and remittances up to Rs 45,000, will be made through green-channel all banking, which was introduced because 26 out of 680 branches of the bank in the first phase, the all bank’s General Manager (Network-II), Devendra Prasad, said on Wednesday. This is all India promotes green channel.